Розробка комп’ютерної гри жанру «top-down rpg» для ОС Windows - Солодкий, Д. В. (ХНУРЕ, 2024)
The main goal of developing Top-down RPG PC game for Windows operating system is to create an engaging gaming experience. The focus is on providing players with an immersive world and immersive gameplay. Key features of the game include a well-thought-out plot, dynamic interaction of characters. To increase user engagement and retention, the game incorporates various game design elements such as an interactive environment, different gear. In addition, the implementation of a reliable inventory system, character development and a visually appealing game world contribute to the overall enjoyment of the game.
Keywords: top-down rpg; комп’ютерна гра; розробка гри; ОС Windows; ігровий жанр